If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5x = 10 Combine like terms: 3x + -5x = -2x -2x = 10 Solving -2x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = -5 Simplifying x = -5
| 4-144y^2=-18 | | -7-6x=9-9x | | 5j^3-80j=0 | | x^2+12x=5x | | 37.5(x+4)=6.6 | | 560-13m=365 | | 4(x+7)=-24 | | 4a-2b+5b= | | x^2+3x+5=5 | | -6+b=17 | | 7q^2-28=0 | | 2s^2+9s^2+s^2= | | x^2+28x-45173=0 | | -9(x+6)-9=-63 | | 2s^2+9s^2=s^2 | | x^2-6x+5=5 | | 4+(x+8)=2(2x+6)+20 | | 16x^2-10x-8= | | -(x+8)+9=9x+1-10x | | 37.5(x+400)=6.6666 | | 24x^2-11x-8= | | 6(3y-1)-3(2y)=26 | | 24x^2-10x-8= | | 36+x^2=100 | | -(7-m)=-(5m+7) | | 7(t-2)-t= | | 0=9a^2-4a | | 22x^2-11x-8= | | x^2+2x-4=-2x+1 | | 22x^2-10x-8= | | 22x^2-31x-8= | | -8x-11(x+5)=-2(9x+2) |